The upstream sequence element of the C2 complement poly(A) signal activates mRNA 3' end formation by two distinct mechanisms. - Moreira, A; Takagaki, Y; Brackenridge, S; Wollerton, M; Manley, J; Proudfoot, N (1998)
The poly(A) signal of the C2 complement gene is unusual in that it possesses an upstream sequence element (USE) required for full activity in vivo. We describe here in vitro experiments demonstrating that this USE enhances both the cleavage and poly(A) addition reactions. We also show that the C2 USE can be cross-linked efficiently to a 55-kD protein that we identify as the polypyrimidine tract-binding protein (PTB), implicated previously in modulation of pre-mRNA splicing. Mutation of the PTB-binding site significantly reduces the efficiency of the C2 poly(A) site both in vivo and in vitro. Furthermore, addition of PTB to reconstituted processing reactions enhances cleavage at the C2 poly(A) site, indicating that PTB has a direct role in recognition of this signal. The C2 USE, however, also increases the affinity of general polyadenylation factors independently for the C2 poly(A) signal as detected by enhanced binding of cleavage-stimulaton factor (CstF). Strikingly, this leads to a novel CstF-dependant enhancement of the poly(A) synthesis phase of the reaction. These studies both emphasize the interconnection between splicing and polyadenylation and indicate an unexpected flexibility in the organization of mammalian poly(A) sites.